2012
DOI: 10.1016/j.neuroimage.2011.10.099
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two itches. Common features and notable differences in brain activation evoked by cowhage and histamine induced itch

Abstract: Previous PET and fMRI brain imaging studies targeting neural networks processing itch sensation have previously used histamine as the sole itch inducer. In contrast with histamine, cowhage-induced itch is mediated via proteinase activated receptors PAR2 and is transmitted through a separate spinothalamic pathway, therefore imaging the brain activation evoked by cowhage could provide further insight central processing of itch. We report for the first time a functional MRI Arterial Spin Labeling (ASL) study of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
164
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(183 citation statements)
references
References 39 publications
(62 reference statements)
10
164
3
6
Order By: Relevance
“…In a PET study, a positive correlation was found between the subjective intensity of histamine evoked itch sensation and the activity of the insula and the anterior cingulate cortex [43]. Moreover, Papoiu and colleagues [44] identified different cerebral activity patterns in itch evoked by histamine or cowhage.…”
Section: Higher Itch Centersmentioning
confidence: 98%
See 1 more Smart Citation
“…In a PET study, a positive correlation was found between the subjective intensity of histamine evoked itch sensation and the activity of the insula and the anterior cingulate cortex [43]. Moreover, Papoiu and colleagues [44] identified different cerebral activity patterns in itch evoked by histamine or cowhage.…”
Section: Higher Itch Centersmentioning
confidence: 98%
“…Among them, PAR2, expressed by sensory neurons, is considered as a key molecule in itch sensation [66][67][68]. In experimental models, by using cowhage spicules (which contain the protease mucunain) to activate PAR2, a histamine-independent parallel itch pathway was identified and found to significantly contribute to chronic itch sensation [10,27,44,69,70]. Interestingly, the activation of PAR2 by kallikrein (a tryptic enzyme) related proteases was also shown in epidermal keratinocytes [71] which further argue for the impact of the pathway in pruriceptive itch.…”
Section: Proteases and Their Receptorsmentioning
confidence: 99%
“…In klinischen Studien klagten Frauen häufi ger über Schmerzen, die länger andauerten und intensiver waren als bei Männern (Unruh 1996). In experimentellen Studien zu diesem Thema wiesen Frauen eine niedrigere Schmerzschwelle (Riley et al 1998) (Kleyn et al 2012;Papoiu et al 2012). Der lentiforme Nucleus nimmt dabei eine modulierende Rolle im sog.…”
Section: Geschlechtsspezifi Sche Physiologische Unterschiede In Der Punclassified
“…L'activation de ces récepteurs ne s'accompagne d'ailleurs pas d'une papule oedémateuse, contrairement à celle qui accompagne la réaction à l'activation des récepteurs de l'histamine. Elle est suivie par l'activation de neurones différents des neurones histaminergiques dans la moelle épinière [13], puis dans le cerveau [14]. Ce n'est que dans un deuxième degré de différenciation avec les nocicepteurs est encore l'objet de débats [4].…”
Section: Des Médiateurs Multiplesunclassified
“…Ainsi, le cortex somato-sensoriel, le cortex pariétal, des aires motrices (cortex moteur primaire, aire motrice supplémentaire, cortex pré-moteur), le cortex préfrontal, le gyrus cingulaire antérieur, l'insula ou le mésencéphale sont activés en cas de prurit. Le claustrum, l'insula, les ganglions basaux, le putamen et le thalamus sont plus activés par le cowhage que par l'histamine [14]. Le processing cérébral du prurit est très sensible à la température [30].…”
Section: Deux Grandes Voies Relayant La Sensation De Pruritunclassified